PENGARUH PROFITABILITAS, DER, KUALITAS KAP DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - lailatus Sa’adah; Reza Santikasari (STIE Malangkucecwara Malang) (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2020)
This study aims to determine whether the profitability, DER, quality of KAP and company size affect the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange. The sample of this study used 108 manufacturing companies that were consistently listed on the Indonesia Stock Exchange for the period 2016 - 2018 which were taken using the purposive sampling method. These factors were then tested using logistic regression at a significance level of 5 percent. The results of the study identified that profitability as measured by Return On Assets, Debt to Equity Ratio, Public Accounting Firm Quality, and Company Size had no effect on the Timeliness of Financial Reporting in manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 - 2018.